Current Cost Accounting: Identifying the Issues (Book). - Kam, Vernon; Burns, Thomas J. (The Accounting Review, 1979)
Abstract Reviews the book "Current Cost Accounting: Identifying the Issues," edited by Don T. DeCoster, Kavasseri V. Ramanathan.